Marriage continues to protect: Social support, stress, and perceptions of health just prior to the COVID-19 pandemic using cross-sectional data from a crowdsourced survey in the United States - Adrian J. ARCHULETA (Journal of Health and Social Sciences)
Introduction: Most studies have focused on the effects of the COVID-19 lockdown on social relationships. However, few studies have examined differences in health, social support, perceived stress, and quality of life (QoL) just prior to the COVID-19 pandemic in the United States (U.S.). Historically, marriage has been a protective factor that buffers psychological distress and enhances a person's QoL. Yet, it is unclear whether some relationship groups entered the pandemic with these protective benefits over others. Therefore, the current study examines differences between relationship status groups' subjective assessment of health, stress, and social support prior to the widespread effects of COVID-19 in the United States. Methods: In this study, data were used from a cross-sectional social network study completed just prior to the COVID-19 pandemic in the U.S. Individuals between the ages of 18 and 65 (N =284) years were recruited from a crowdsource platform to complete health, social support, and perceived stress measures. Results: Among the sample, 66% reported psychological QoL scores below 60, followed by social QoL (60%), environment QoL (48%), and physical QoL (39%). Bivariate results identify positive correlations between social support, social network size, and QoL domains. Conversely, perceived stress was negatively correlated with these variables. ANCOVA results indicate that those who were married reported significantly higher psychological (F3, 275 = 3.73, p = .012), social (F3, 275 = 16.50, p < .001), and environmental (F3, 275 = 6.03, p < .001) QoL and less stress (F3, 275 = 5.75, p < .001) than single or cohabiting individuals. However, those in a committed relationship (not cohabiting) did not substantially differ from those who were married. Discussion: Some groups entered the COVID-19 pandemic with greater protective benefits than others. In the current study, those who were married and in a committed relationship reported better QoL compared to other groups. Understanding the protective benefits experienced by particular groups may help policymakers, healthcare professionals, and service providers understand the full impact of the COVID-19 pandemic.